KAITAN PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN ASET DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Setyawati, Silvi; Dermawan, Elizabeth Sugiarto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted with the aim of knowing the relationship between profitability, liquidity, asset growth, and company size on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This study used a sample of 176 data. The sample selection technique in this study was purposive sampling using SPSS version 26 and Microsoft Office Excel. The results showed that profitability has a weak, negative, and significant correlation to capital structure, liquidity has a moderate, negative, and significant correlation to capital structure, asset growth has a weak, positive, and insignificant correlation to capital structure, and firm size has a moderate, positive correlation. and significant to the capital structure.